The Rhetoric of the Qur’anic Rhythm in the Verses beginning with Alam Tara (Have you not seen?) from Surat Al-Baqarah - Bin Direi, Mohammed Bin Ali Bin Aith (Arts for Linguistic & Literary Studies, 2023)
The research aims to study the rhetoric of Qur’anic rhythm in the verses beginning with Alam Tara (Have you not seen?) from Surat Al-Baqarah. It is organized into a preface and two sections preceded by an introduction and followed by a conclusion. The preface deals with the definition of Surat Al-Baqarah, and the introduction reveals the importance of the research, the reasons for its selection, its objectives, previous studies, its methodology, and its plan. The first section dealt with the analytical study of the three verses with the aim of understanding their context, studying them, employing the arts of rhetoric and their values, deducing the characteristics of the Qur’anic systems in them, and analyzing them in a way that reveals their secrets. The research concluded that the connection of the context of the three verses to the general context of the surah made it a cohesive structure like a single unit. The precision in choosing words, the beauty and strength of their timbre, and the difference in their form are manifestations of clarity. The styles of departing from the original, such as advancing, deferring, definite, indefinite, separation, connection, shortening, brevity, and the diversity of the verses into declarative and non-declarative sentences, nominal and verbal, and their noticeable prominence in the verses is a manifestation of strength and beauty